An Investigation of Engineering Technology Students’awareness and Basic Understanding of Industrial Revolution 4.0 (IR4.0) - Alias, Muhammad Najhan; Azmil, Muhd Afiq; Qushairi Ahmad Sukri, Ahmad Farhan; Ahmad, Norkhairi (English Education Study Program Faculty of Teacher Training and Education, 2024)
The Industrial Revolution 4.0 (IR4.0) is a novel transformative concept that entails a lot of changes to the way the community function. It has brought about significant changes in various workplace and industries, This study aims to assess the level of awareness on IR4.0 and the understanding of the technology pillars among 1st year engineering technology students of a private university via survey method and interview session. The findings show that the students have a fair knowledge of IR4.0 concept acquired from a number of sources and they are in the midst of learning more on this, via integration of the information into the curriculum, campus environment and activities with lecturers and fellow students. The students are positively impacted by the presence of IR4.0 within their study context and environment. This study will provide valuable insights into the current knowledge and perception of IR4.0 among university students, by highlighting areas for improvement in educational curriculum and industry readiness. As future leaders and new members of society it is crucial for them to have a deep understanding and awareness of its impact in life.